2000
DOI: 10.1046/j.1440-0979.2000.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent and stable housing for individuals living with a mental illness in the community: A paradigm shift in attitude for mental health nurses

Abstract: The provision of appropriate housing for individuals with a mental illness has been recognized by a number of researchers as a means to enhance effectiveness of treatment and rehabilitation services, to maintain treatment gains, and to decrease community opposition to deinstitutionalization. Whether community-based services, which are now meant to be the focus of treatment, are successful or not is crucially related to the nature and availability of accommodation. This paper argues a case for change in the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
(18 reference statements)
1
19
0
1
Order By: Relevance
“…These include living in hospitals, boarding houses, hostels and group homes with varying degrees of supervision, living with parents and independent living in the person's own home with a choice of house mates/partners. There is consensus in the literature that, outside hospital, the most desirable accommodation is independent housing, whilst the least desirable is boarding houses (Anthony & Blanch, 1989;Baker & Douglas, 1990;Carling, 1989Carling, , 1990Carling, & 1993Cleary et al, 1998;Health Care Complaints Commission, 1996;Howie the Harp, 1990;Linhorst, 1991;Moxam & Pegg, 2000;Posey, 1990;Strong, 1995).…”
Section: Types Of Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…These include living in hospitals, boarding houses, hostels and group homes with varying degrees of supervision, living with parents and independent living in the person's own home with a choice of house mates/partners. There is consensus in the literature that, outside hospital, the most desirable accommodation is independent housing, whilst the least desirable is boarding houses (Anthony & Blanch, 1989;Baker & Douglas, 1990;Carling, 1989Carling, , 1990Carling, & 1993Cleary et al, 1998;Health Care Complaints Commission, 1996;Howie the Harp, 1990;Linhorst, 1991;Moxam & Pegg, 2000;Posey, 1990;Strong, 1995).…”
Section: Types Of Housingmentioning
confidence: 99%
“…There is substantial support for this view in Australia (Burdekin, Guilfoyle & Hall, 1993;Queensland Health, 1996) and internationally (World Health Organization, 1990). Without the availability of quality affordable housing, other treatment and rehabilitation approaches are jeopardized (Moxam & Pegg, 2000;Stroul, 1989). This view is also well supported by research (Anthony & Blanch, 1989;Baker & Douglas, 1990;Rosenfield, 1990;Stroul, 1989).…”
Section: Introductionmentioning
confidence: 98%
“…L'espoir est aussi lié à l'autodétermination, définie comme la confiance en ses propres capacités et le contrôle sur sa vie, et qui constitue une autre valeur clé que Parkinson (2003) a documentée à l'aide du récit d'usagers et usagères bénéficiant de divers types d'hébergement structuré. Moxham et Pegg (2000) ont rapporté que le respect des besoins et du choix des usagers et usagères contribuait au développement de leurs capacités d'autodétermination et était essentiel à leur réinsertion dans la communauté. Toutefois, une étude a démontré que des personnes âgées devaient souvent faire un compromis entre leur préférence d'hébergement et leurs besoins en termes de sécurité et de protection (Boydell, 2006 ;Whitley, Harris et Drake, 2008), ce qui est également le cas pour les usagers et usagères des services en santé mentale (Forchuk, Nelson et al, 2006).…”
Section: L'espoir Et L'autodéterminationunclassified
“…Warren and Bell's (2000) Australian study, investigating user views of accommodation, concluded that users gave priority to privacy and safety, rejecting designated group homes because of associated stigma. Also in Australia the importance of housing in underpinning social integration and personal independence is emphasised (Moxham and Pegg 2000): the benefits of user involvement in housing provision is illustrated in a report by Bond (1999), describing a housing project funded by the voluntary sector.…”
Section: Accommodation Servicesmentioning
confidence: 99%